Dielectric properties of powder-sol-derived strontium barium niobate/strontium barium titanate composite ceramics. (2nd January 2018) - Wang, Fengchun; Wu, Ze; Shan, Lianwei; Dong, Limin; Zhang, Xianyou
ABSTRACT: In this paper, strontium barium niobate/strontium barium titanate [Srx Ba1-x Nb2 O6 /Srx Ba1-x TiO3 ] composite ceramics with different Sr 2+ /Ba 2+ ratio were fabricated using a Powder-Sol (P-S) method. The formation process of SBN/SBT was studied by TG-DTA. It is found that the tetragonal tungsten bronze (TTB) phase and perovskite phase were co-present in the composite ceramics, and the Sr 2+ /Ba 2+ ratio has an influence on the proportion between SBN and SBT. SEM results show that samples are homogeneous and fine-grained. The dielectric properties of composite ceramics were studied by impedance analyzer, and indicates that the dielectric constant and dielectric loss could be well regulated by Sr 2+ /Ba 2+ ratio.